Nowcasting national GDP growth using small business sales growth - Cahit Guven (Global Labor Organization (GLO), 2022)
This study shows that the Xero Small Business Index (XSBI) monthly sales growth data can be used to predict the same period's nominal gross domestic product (GDP) growth (year-on-year) in the United Kingdom, Australia and New Zealand.1 Assuming that the small business sector can be used as a representative sample of the national economy,2 this paper presents simple equations relating the small business real-time sales growth to GDP growth indicators. One of the frustrations of GDP measurement is that it takes statistical offices many weeks to collate GDP data. This means it is often released months after the end of the relevant time period. The relationship with XSBI sales growth data, which is published more timely, could prove useful for economists and analysts as an early indication of GDP results weeks ahead of the release of official data. This analysis does not relate to using XSBI data to forecast future GDP. Rather it is to take advantage of the timeliness of XSBI data, over the national accounts release, and provide an early indication of the GDP data after the end of the relevant month/quarter but before the official GDP data is released.
Keywords: 330